2005
DOI: 10.1103/physreva.72.043409
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling in an optical lattice that employs Raman transitions

Abstract: We demonstrate laser cooling in an optical lattice that employs Raman transitions. Four laser beams with different frequencies form a one-dimensional lattice with a basic lattice period that is a factor of 2 less than in standard optical lattices. Rb atoms are cooled to 8 K. We measure the intensity-and detuning-dependence of the cooling mechanism. Our experimental results agree well with theoretical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The radial matrix element in Eq. (14) can be deduced from the measured lifetime of the excited state, which yields in our case 5S 1/2 er 5P 1/2 = √ 3(2.9919 ± 0.0030) ea 0 [25,26]. Note that the factor of √ 3 stems from the angular integration since we consider the radial matrix element in our calculations.…”
Section: Van Vleck Perturbation Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…The radial matrix element in Eq. (14) can be deduced from the measured lifetime of the excited state, which yields in our case 5S 1/2 er 5P 1/2 = √ 3(2.9919 ± 0.0030) ea 0 [25,26]. Note that the factor of √ 3 stems from the angular integration since we consider the radial matrix element in our calculations.…”
Section: Van Vleck Perturbation Theorymentioning
confidence: 95%
“…Note that the factor of √ 3 stems from the angular integration since we consider the radial matrix element in our calculations. The individual contributions of the matrix (14) can be interpreted as follows. The diagonal elements stem from the lightshift potential of the lasers, that is, the off-resonant coupling of a m F component of the ground state to an excited state.…”
Section: Van Vleck Perturbation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of real-time spatial imaging of the structures with sub-wavelength period is of particular interest for study cold atoms in optical lattice [7]. …”
mentioning
confidence: 99%
“…A dominant feature of the recent experiment [10] was high loss rates, attributed to non-adiabatic Landau-Zener transitions [14]. We should mention other methods which may be adapted to increase on-site interactions in a lattice include tunable scattering lengths and Feshbach resonances [15,16], and other methods proposed to give sub-half-wavelength structure to optical lattices, for example Raman processes [17,18].The phase transition from the superfluid state ceases to be adiabatic when the inverse timescale 1/τ becomes of the same order of magnitude as the frequencies of the lowest lying excitations, which are ∼ U in the limit U ≫ J; increasing U will decrease the number fluctuations in the final state. Furthermore, when finite temperature effects are taken into account, it has been shown that increasing U increases the purity of the final state [19], as one would expect from thermodynamic considerations.…”
mentioning
confidence: 99%